Results of Using Spersal Chemical Meliorant to Improve The Reclamation State of Saline Soils in The Kashkadarya Region - Doniyorov Toshmamat Omonovich; Kuvatov Ulugbek Jalolovich (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2024)
The article presents the results of experiments conducted in the Karshi district of the Kashkadarya region to improve the reclamation condition of moderately saline soils, enhance the efficiency of irrigated land use, and achieve higher crop yields. Considering the region’s water scarcity, a water-saving “Chemical” method was employed to improve the reclamation state of saline soils. To ensure the leaching of salts to lower soil layers, irrigation rates exceeding the standard by 25% and 50% under water scarcity conditions were applied, and these methods were compared with traditional approaches to study the soil’s water-salt regime. The chemical ameliorant SPERSAL, recommended by the Swiss company “Sibo-Novartis,” was used as a soil amendment at a rate of 5 kg/ha. When applied to the soil before irrigation or mixed with irrigation water, SPERSAL induces an ion exchange reaction in the soil adsorption complex, displacing sodium cations with calcium and magnesium cations. Salts such as sodium chloride, sodium sulfate, and sodium bicarbonate formed in the plant root zone dissolve in irrigation water and leach into lower soil layers. Key parameters studied include soil water absorption, field capacity, capillary rise height of soil moisture, the amount of water-soluble salts in irrigation, drainage, and groundwater, as well as soil moisture dynamics. Calculations for the water required for leaching and irrigation of saline soils, along with the economic efficiency of the applied variants based on cotton yields, were determined according to the “Methods of Conducting Field Experiments” (Tashkent, 2007) guidelines.